Effect of Ti addition and cast part size on solidification structure and mechanical properties of medium carbon, low alloy cast steel - Nicolás Emanuel Tenaglia; Diego Fernandino; Alejandro Daniel Basso (Fracture and Structural Integrity)
In this work, the effect of Ti addition and the cast part size on the solidification structure and mechanical properties of a medium carbon, low alloy cast steel was analyzed. The experimental analysis involved the design of the melts by using Thermo-Calc® software, where different amounts of Ti added to a standard chemical composition of an AISI 13XX steel were simulated. Then, the solidification macrostructure (dendritic pattern and grain size) and microstructure were characterized by using conventional and specific metallographic techniques. Finally, the mechanical behavior in terms of hardness and tensile properties were evaluated.